Blade design optimisation for fixed-pitch fixed-speed wind turbines - Wang, Lin; Tang, Xinzi; Liu, Xiongwei (Hindawi Publishing Corporation, 2012)
Fixed-pitch fixed-speed (FPFS) wind turbines have some distinct advantages over other topologies for small wind turbines, particularly for low wind speed sites. The blade design of FPFS wind turbines is fundamentally different to fixed-pitch variable-speed wind turbine blade design. Theoretically, it is difficult to obtain a global mathematical solution for the blade design optimisation. Through case studies of a given baseline wind turbine and its blade airfoil, this paper aims to demonstrate a practical method for optimum blade design of FPFS small wind turbines. The optimum blade design is based on the aerodynamic characteristics of the airfoil, that is, the lift and drag coefficients, and the annual mean wind speed. The design parameters for the blade optimisation include design wind speed, design tip speed ratio, and design attack angle. A series of design case studies using various design parameters are investigated for the wind turbine blade design. The design outcomes are analyzed and compared to each other against power performance of the rotor and annual energy production. The design outcomes from the limited design cases demonstrate clearly which blade design provides the best performance. This approach can be used for any practice of FPFS wind turbine blade design and refurbishment.